The temporospatial epidemiology of rheumatic heart disease in Far North Queensland, tropical Australia 1997-2017; impact of socioeconomic status on disease burden, severity and access to care. - Katherine Kang; Ken W T Chau; Erin Howell; Mellise Anderson; Simon Smith; Tania J Davis; Greg Starmer; Josh Hanson (Public Library of Science (PLoS), 2021)
Background The incidence of rheumatic heart disease (RHD) among Indigenous Australians remains one of the highest in the world. Many studies have highlighted the relationship between the social determinants of health and RHD, but few have used registry data to link socioeconomic disadvantage to the delivery of patient care and long-term outcomes. Methods A retrospective study of individuals living with RHD in Far North Queensland (FNQ), Australia between 1997 and 2017. Patients were identified using the Queensland state RHD register. The Socio-Economic Indexes for Areas (SEIFA) Score-a measure of socioeconomic disadvantage-was correlated with RHD prevalence, disease severity and measures of RHD care. Results Of the 686 individuals, 622 (90.7%) were Indigenous Australians. RHD incidence increased in the region from 4.7/100,000/year in 1997 to 49.4/100,000/year in 2017 (p<0.001). In 2017, the prevalence of RHD was 12/1000 in the Indigenous population and 2/1000 in the non-Indigenous population (p<0.001). There was an inverse correlation between an area's SEIFA score and its RHD prevalence (rho = -0.77, p = 0.005). 249 (36.2%) individuals in the cohort had 593 RHD-related hospitalisations; the number of RHD-related hospitalisations increased during the study period (p<0.001). In 2017, 293 (42.7%) patients met criteria for secondary prophylaxis, but only 73 (24.9%) had good adherence. Overall, 119/686 (17.3%) required valve surgery; the number of individuals having surgery increased over the study period (p = 0.02). During the study 39/686 (5.7%) died. Non-Indigenous patients were more likely to die than Indigenous patients (9/64 (14%) versus 30/622 (5%), p = 0.002), but Indigenous patients died at a younger age (median (IQR): 52 (35-67) versus 73 (62-77) p = 0.013). RHD-related deaths occurred at a younger age in Indigenous individuals than non-Indigenous individuals (median (IQR) age: 29 (12-58) versus 77 (64-78), p = 0.007). Conclusions The incidence of RHD, RHD-related hospitalisations and RHD-related surgery continues to rise in FNQ. Whilst this is partly explained by increased disease recognition and improved delivery of care, the burden of RHD remains unacceptably high and is disproportionately borne by the socioeconomically disadvantaged Indigenous population.